Inability of infants to push up in the prone position and subsequent development. Issue 9 (8th August 2018) - Senju, Ayako; Shimono, Masayuki; Tsuji, Mayumi; Suga, Reiko; Shibata, Eiji; Fujino, Yoshihisa; Kawamoto, Toshihiro; Kusuhara, Koichi
Abstract: Background: During routine health screening, some infants cannot maintain the prone position with extended arm support at 6 months. Little is known, however, about the development of full‐term infants with this developmental deviation. We investigated the developmental course of infants with this characteristic. Methods: We enrolled 2, 020 full‐term infants who had been recruited at a regional center for the Japan Environment and Children's Study. Their development was measured using the Ages and Stages Questionnaire, third edition, at 0.5, 1, 1.5, 2, 2.5, and 3 years. The children were grouped according to their ability to stay prone on extended arms at 6 months, and their development was compared. Results: A total of 1, 625 infants could stay prone on extended arms and 179 could not. We excluded 212 infants who could stay prone on extended arms only sometimes, and four who did not have a questionnaire response. In the gross motor domain, significant difference in questionnaire scores was observed between the "could" and "could‐not" groups at 6 months (Hedges' g, 1.83) and persisted until 3 years (Hedges' g, 0.33). Significant differences were also observed in the communication, fine motor, problem solving, and personal–social domains at 6 months (Hedges' g, 0.20–0.58) and persisted until 1, 2, 2, and 1.5 years, respectively (Hedges' g, 0.21–0.25). Conclusions: Infants who cannot maintain the prone position on extended arms lag behind those who can, although the effect sizes become relatively small after 1.5 years of age. Early intervention may be considered if delay is problematic or persistent.